Synthesis,Characterization and Evaluation of the Anticancer and Antimicrobial Activities of Some Novel Benzazole and Benzazine Derivatives (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
The present study was designed to synthesize  and develop new useful lead compounds (some novel benzazole and benzazine derivatives ) of simple structure , exhibiting optimal in vitro anticancer  and antimicrobial potency. Phenylenediamine derivative 1 was condensed  with  dithiocarboxylic acid derivatives 2 and produced   benzimidazole derivative 4. The benzotriazepines 8 and 10  were formed by the reaction of 1 with dicarbonyl derivatives followed by intermolecular coupling reaction. The synthesis of benzotriazine12, benzotriazole 14,17, benzimidazole16 and benzothiadiazine 19 from compound 1 was also described. The Synthesized Compounds were characterized by Spectral Studies like IR, H1 – NMR and Analysis Spectra .The title compounds were screened for their possible In vitro anticancer and antimicrobial activities. Among the synthesized compounds, some have shown promisingly remarkable activities against  different  cancer cell lines (MCF-7 human breast cancer cells, HepG2 human hepatocarcinoma cells and PC3 human prostate cancer cells)and moderate  to high antibacterial and antifungal activities. The obtained results showed that the most active compounds could be useful as a template for future design, modification and investigation to produce more active analogs.